2016
DOI: 10.1186/s12944-016-0377-2
|View full text |Cite
|
Sign up to set email alerts
|

Combination of aspirin with essential fatty acids is superior to aspirin alone to prevent or ameliorate sepsis or ARDS

Abstract: It has been suggested that aspirin may be of benefit in treating sepsis and ARDS in view of its ability to block cyclo-oxygenase-1 (COX-1) and COX-2 activities; inhibit nuclear factor kappa B (NF-κB); enhance the production of endothelial nitric oxide (eNO) and lipoxin A4 (LXA4). Our previous studies revealed that plasma phospholipid content of arachidonic acid (AA) and eicosapentaenoic acid (EPA) is low in patients with sepsis. This implies that beneficial actions of aspirin in sepsis and ARDS is unlikely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Monteiro et al ( 35 ) demonstrated that the products of ALOX5 induced lung injury during sepsis. Furthermore, ALOX5 expression in a mouse model exacerbated sepsis-induced multiple organ injury ( 36 ) and mice with an increased susceptibility to sepsis exhibited increased ALOX5 expression ( 37 ). In the present study, ALOX5 expression was significantly upregulated in blood samples from patients with sepsis compared with controls, and ALOX5 was determined to have a high diagnostic value, indicating that ALOX5 may have a crucial role in the inflammatory and immune processes of sepsis and has potential as a diagnostic marker.…”
Section: Discussionmentioning
confidence: 99%
“…Monteiro et al ( 35 ) demonstrated that the products of ALOX5 induced lung injury during sepsis. Furthermore, ALOX5 expression in a mouse model exacerbated sepsis-induced multiple organ injury ( 36 ) and mice with an increased susceptibility to sepsis exhibited increased ALOX5 expression ( 37 ). In the present study, ALOX5 expression was significantly upregulated in blood samples from patients with sepsis compared with controls, and ALOX5 was determined to have a high diagnostic value, indicating that ALOX5 may have a crucial role in the inflammatory and immune processes of sepsis and has potential as a diagnostic marker.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , it is reasonable to assume that in critically ill patients such as those suffering from sepsis-recovery or succumbing to disease depends on the ability of tissues to produce adequate amounts of LXA4/resolvins/protectins/maresins at the right time to resolve inflammation and initiate tissue repair. It is also likely that inappropriate production of LXA4/resolvins/protectins/maresins at inappropriate time such as in the beginning of sepsis process may suppress much needed inflammation and lead to worsening of the illness [59] , [60] , [61] , [62] . Thus, production of adequate amounts of PGE2/LTs and other pro-inflammatory molecules including ILs, TNF-α and anti-inflammatory molecules (lipoxins/resolvins/protectins/maresins/IL-4, IL-10/IL-13) at the most appropriate times of any illness are critical that ultimately determines recovery or death.…”
Section: Pgs Lxa4/resolvins/protectins/maresins and Lts Modulate Mamentioning
confidence: 99%
“…For example, our study showed that cluster 2 identified by the black module was associated with lower survival probability, and this subtypes of sepsis was characterized by leukocyte activation. Such over-activation of inflammatory response may indicate that immunoregulatory agents such as arachidonic acid and eicosapentaenoic acid can help to improve the survival outcome [39]. Mortality is an important clinical trait and thus we tried to identify modules most significantly assocated with mortlaity.…”
Section: Discussionmentioning
confidence: 99%